Principles of clinical electrocardiography - Goldman, Mervin J. (Lange Medical Publications, 1986)
This volume introduces the basic concepts of electrocardiography and their clinical applications. A knowledge of basic electrophysiologic principles is essential in the understanding of the ECG. These principles are emphasized throughout the text and foster understanding, rather than rote memorization, in the inter- pretation of the ECG. This permits a more logical and meaningful appre- ciation of electrocardiography.